An injectable composite filler and a preparation method thereof

Through the combination of silk fibroin microspheres and sodium hyaluronate and the inducible chitosan/sodium alginate/sodium hyaluronate thermosensitive hydrogel, the self-supporting properties of existing fillers in facial filling and the self-supporting properties of existing fillers and the The problem of insufficient degradation time has achieved high injection and long-term shaping effects, which are suitable for facial and tissue repair.

CN118384329BActive Publication Date: 2024-12-27MEIDIAN BIOTECHNOLOGY (BEIJING) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410494249.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2024-12-27
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

When filling the face, existing fillers have problems such as insufficient self-support, poor tissue fusion, short degradation time, safety hazards and injection inequality, especially the high viscosity and elasticity requirements of silk fibroin microspheres during injection. Improper control can easily lead to agglomeration and blockage of the needle, resulting in failure of the injection.

Method used

Using fillers combined with silk fibroin microspheres and sodium hyaluronate hydrogels, the mass ratio of silk fibroin microspheres (5-200μm) with specific molecular weight and particle size distribution to sodium hyaluronate is greater than 1. Fillers, covalent crosslinking using crosslinking agents and chemical initiators, improve mechanical properties and injection properties, and modify them by inducing chitosan/sodium alginate/sodium hyaluronate thermosensitive hydrogels and ketothyol/calcium The combination of silk fibroin microspheres achieves stability and degradation control.

Benefits of technology

It achieves high injection properties, controllable mechanical properties, long-term shaping cycle and biosafety, avoids microsphere aggregation and injection difficulties, extends the use time of fillers, reduces production costs, and is suitable for facial filling and tissue repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118384329B_ABST
    Figure CN118384329B_ABST
Patent Text Reader

Abstract

The present invention proposes an injectable composite filler and a preparation method thereof, belonging to the technical field of fillers. The composite filler is composed of microspheres and hydrogels, the particle size distribution range of the microspheres is 5-200 μm; the surface charge is ‑50 to 25 mV, the microspheres are silk fibroin microspheres, the hydrogel is sodium hyaluronate hydrogel, the sodium hyaluronate is pure sodium hyaluronate and its derivatives or modified sodium hyaluronate, and the mass ratio of silk fibroin to sodium hyaluronate in the composite filler is greater than 1. The composition of the material of the injectable composite filler prepared by the present invention is closer to human tissue and the thermal stability of the material is better, the in vivo safety and the effective support period are longer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fillers, and in particular to an injectable composite filler and a preparation method thereof. Background Art

[0002] With the continuous improvement of medical technology, the treatment of medical cosmetic surgery is becoming more and more minimally invasive, efficient and safe. Injection micro plastic surgery is to use natural or synthetic fillers, which are injected into the dermis or subcutaneous layer of the human body to improve the facial shape and achieve rejuvenation. It mainly includes improving facial contours, correcting wrinkles, supporting loose skin, filling sunken scars, and repairing injured tissues. Injection micro plastic surgery has become more and more prominent in plastic surgery.

[0003] In terms of dermal or subcutaneous filling, injectable hydrogel materials with self-support, tissue fusion, degradability and biosafety have attracted much attention. At present, the most common products on the market as facial soft tissue fillers are sodium hyaluronate and collagen. Sodium hyaluronate is a linear high-molecular polysaccharide composed of N-acetylglucosamine and gluconic acid disaccharide units, and its viscoelasticity and moisturizing properties are particularly outstanding. There are many problems when used as a skin filler. Non-cross-linked or low-cross-linked sodium hyaluronate is prone to displacement at the injection site, which is seriously inconsistent with the tissue around the injection point (hyaluronic acid face). In addition, the degradation rate is too fast, the shaping time is short (2-3 months), and multiple injections are required. Highly cross-linked sodium hyaluronate has high hardness, insufficient elasticity, and is difficult to push. After subcutaneous or dermal injection, it has a blocky solid feeling, causing tissue discomfort. In addition, the residual amount of cross-linking agent is high. As the gel continues to degrade in the body, the cross-linking agent will be slowly absorbed by the human body, bringing potential toxicity risks to the human body. Collagen fillers are mainly extracted from animal sources such as bovine Achilles tendon and have certain immunogenicity. In addition, collagen has prominent problems such as low mechanical strength, poor plasticity, short degradation time in the body, and short filling effect maintenance period. Therefore, it is urgent to use new technologies to solve the above-mentioned prominent problems that arise during the use of sodium hyaluronate and collagen in facial fillers.

[0004] Unlike the above-mentioned traditional hydrogels, which are composed of continuous polymer network structures, particle composite hydrogels are composed of discontinuous particles evenly distributed in the gel network structure, which are firmly locked under the forces of hydrogen bonding, hydrophobic interaction, electrostatics, steric hindrance, etc. and exhibit stable mechanical properties in the physiological environment. Therefore, particle composite hydrogels have unique advantages in improving self-support, tissue fusion, and durability of shaping effects. For example, polymer microspheres are suspended as structural units in a gel matrix to prepare microsphere composite hydrogels to improve structural properties and mechanical stability. This includes preparing degradable synthetic polymers such as PLLA (polylactic acid), PCL (polycaprolactone), PGA (polycaprolactide), PVA (polyvinyl alcohol), PDO (polydioxanone), P-TMC (polytrimethylene carbonate) into microspheres less than 200 μm, and then dispersing them in cross-linked sodium hyaluronate gel or other polymers, such as CMC (carboxymethyl cellulose), MC (methyl cellulose)) to obtain injectable fillers with a long-lasting and controllable degradation time. When synthetic polymer microspheres enter the body, they trigger a moderate inflammatory response, recruit fibroblasts to wrap the polymer microspheres, secrete collagen, and effectively fill wrinkles caused by subcutaneous collagen loss and collapse, achieving a lasting shaping effect. These fillers also have a series of problems: 1) The cross-linked sodium hyaluronate gel has an uneven degree of cross-linking, irregular particle shape and uneven particle size, which is prone to side effects such as redness and swelling when used for facial filling; 2) The high temperature of moist heat sterilization can easily cause the polymer microspheres and hyaluronic acid to soften, and the shape is difficult to maintain; 3) The addition of surfactants such as CMC (carboxymethyl cellulose) and MC (methyl cellulose) can easily lead to the generation of bubbles, which poses a risk; 4) The degradation rate of polymers in vivo is uncontrollable, and the degradation weight loss is slow at first and fast at the end. The rate at which the degraded polymer monomers stimulate collagen regeneration is difficult to control, which can easily cause side effects such as tissue hyperplasia; 5) The degradation time is short, generally 10 to 20 months, and multiple injections are required; 6) The filler needs to be prepared and used immediately, and it is difficult to ensure the uniformity of the injection; 7) The existing synthetic polymer microsphere technology is mainly based on the emulsion method, which requires the two non-mixed phases (such as water and organic solvent) to be dispersed into an emulsion by stirring, and then further cross-linked and solidified. The residues of organic solvents, surfactants and cross-linking agents pose a safety hazard.

[0005] Natural polymer biomaterials have shown great application potential in tissue engineering and have been widely studied at home and abroad. Silk fibroin is a structural protein with advantages such as excellent plasticity, outstanding mechanical properties, low immunogenicity, extremely high biocompatibility and controllable degradability. It is suitable for a variety of tissue engineering application scenarios and is one of the emerging materials for tissue regeneration. Microgels based on silk fibroin / sodium hyaluronate composite microparticles have been used in vocal cord injury repair, cartilage regeneration and other tissue repair fields, showing excellent tissue repair ability.

[0006] In the Chinese invention patent "An injectable microsphere gel of silk protein with adjustable performance and its preparation method" with publication number CN 115671388 A, a silk protein solution of different molecular weights is screened out by an ultrafiltration system, and then induced by anhydrous ethanol to obtain silk protein nano-micron particles (30-800nm), which are freeze-dried and re-dissolved, and then a gel inducer is added and stirred to form a uniform and stable silk protein microsphere gel. Although the gel is thixotropic and has the rheological behavior of a fluid when subjected to shear force, and can have a certain self-supporting shape when standing still, the gel needs to be added with a gel inducer, which poses a safety risk. In addition, the particle size of the particles in the gel is 30-800nm, the degradation cycle is short, and the shaping durability is difficult to maintain. The Chinese invention patent "A structural protein / hyaluronic acid composite micro-nano particles and particle hydrogel materials and applications" with publication number CN 115521627 A is to blend structural protein with sodium hyaluronate to form a uniform blend phase, form a suspension (20nm~5μm) under the action of a polarity inducer, add a cross-linking agent to the suspension, continue the reaction, repeatedly centrifuge and wash to obtain a structural protein / hyaluronic acid composite micro- and nanoparticle dispersion, and freeze-dry and re-dissolve to obtain an injectable gel with composite microsphere particles as the basic structural unit. The control conditions for obtaining a uniform structural protein / sodium hyaluronate blend are difficult, the method is complex, and polarity inducers and cross-linking agents need to be added. The repeatability and safety need to be verified. In addition, the particle size distribution range is 20nm~5μm, and the shaping durability also needs to be verified.

[0007] The durability of facial shaping is closely related to the particle size distribution and morphology of the polymer microspheres in the filler. The particle size distribution of polymer microspheres is more advantageous when it is between 30-50μm. At present, there are many methods for preparing silk fibroin microspheres, and the particle size distribution range of microspheres can be accurately controlled (5μm-200μm). However, the key technology that needs to be broken through is the injectability of silk fibroin microspheres. At present, silk fibroin microspheres have high requirements for the viscosity and elasticity of the dispersion medium during injection. If not properly controlled, they are very easy to agglomerate and clog the needle, resulting in injection failure. So far, there has been no report on the use of silk fibroin microspheres (5μm-200μm) to prepare subcutaneous fillers.

[0008] In view of the limitations of the above-mentioned filling preparations, it has become a technical problem that needs to be solved urgently to develop a sodium hyaluronate composite filler containing silk fibroin microspheres that has strong injectability, stable morphology after high-temperature and moist heat sterilization, self-supporting properties, long shaping cycle, better biosafety, relatively simple methods and easy large-scale production. Summary of the invention

[0009] The purpose of the present invention is to provide an injectable composite filler and a preparation method thereof, which has self-support, tissue fusion, degradability and biosafety and has broad application prospects.

[0010] The technical solution of the present invention is achieved in this way:

[0011] The invention provides an injectable composite filler, which is composed of microspheres and hydrogels. The particle size distribution range of the microspheres is 5-200 μm, and the surface charge is -50 to 25 mV.

[0012] As a further improvement of the present invention, the microspheres are silk fibroin microspheres, the hydrogel is sodium hyaluronate hydrogel, the sodium hyaluronate is pure sodium hyaluronate and its derivatives or modified sodium hyaluronate, and the mass ratio of silk fibroin to sodium hyaluronate in the composite filler is greater than 1.

[0013] Preferably, the molecular weight of the silk fibroin is in the range of 10-350 kDa; the molecular weight of sodium hyaluronate and its sodium hyaluronate derivatives is in the range of 10-20000 kDa.

[0014] As a further improvement of the present invention, the hyaluronic acid derivative is pure sodium hyaluronate modified by functional groups, and the functional groups include: at least one of alkyl, acyl, amino, aldehyde, sulfonic acid, thiol, imidazole, dopamine, catechol, gallic acid, tannic acid, fluorescent group, and dye group. The modified sodium hyaluronate is covalently cross-linked sodium hyaluronate, which is obtained by reacting a compound with a hydroxyl group of a sodium hyaluronate molecular chain. The compound is one or more of acrylic anhydride, acryloyl chloride, methacrylic anhydride, methacryloyl chloride, ethylacrylic anhydride, ethylacryloyl chloride, hydroxyacrylic anhydride, hydroxyacryloyl chloride, isobornyl acrylic anhydride, isobornylacryloyl chloride, allyl isocyanic anhydride, and allyl isocyanyl chloride.

[0015] As a further improvement of the present invention, the preparation method of the silk fibroin microspheres is as follows:

[0016] S1: preparing a regenerated silk fibroin solution, including the steps of degumming, dissolving and purifying silk, and screening and selecting a silk fibroin solution with a specific molecular weight through an ultrafiltration system;

[0017] S2: directly blending the regenerated silk fibroin solution with a specific molecular weight obtained in step S1 with a denaturation inducer, or rapidly drying and then soaking in a denaturation inducer to obtain a silk fibroin microsphere aqueous solution;

[0018] S3: centrifuging and repeatedly washing the silk fibroin microsphere aqueous solution prepared in step S2, and then drying the solution to obtain a redispersible silk fibroin microsphere powder;

[0019] The specific target molecular weight of silk fibroin ranges from 50 to 250 kDa; the concentration of silk fibroin ranges from 0.1 to 40 w / v%, and the denaturation inducer is one or more of alcohols, salts, acids, ketones, nitriles, and furans; the rapid drying method includes spray drying, freeze drying, and natural drying; the blending volume ratio of the silk fibroin and the denaturation inducer is 1 / 1 to 1 / 1000.

[0020] As a further improvement of the present invention, the preparation method of the silk fibroin microspheres is as follows:

[0021] T1: preparing a regenerated silk fibroin solution, including the steps of degumming, dissolving and purifying silk, and screening and selecting a silk fibroin solution with a target molecular weight through an ultrafiltration system;

[0022] T2: directly inducing the formation of gel by ultrasound or incubation based on the regenerated silk fibroin solution with a specific molecular weight obtained in step T1;

[0023] T3: slowly air-drying the silk fibroin gel prepared in step T2 to remove moisture, and then mechanically grinding and pulverizing to obtain redispersible silk fibroin microsphere powder;

[0024] The specific target molecular weight of silk fibroin ranges from 50 to 250 kDa; the concentration of silk fibroin ranges from 0.1 to 40 wt %; the ultrasonic amplitude ranges from 10 to 100%; and the incubation temperature ranges from 20 to 80° C.

[0025] The present invention provides a hyaluronic acid composite filler containing silk fibroin microspheres. The filler material is composed of the aforementioned silk fibroin microspheres as basic structural units. The silk fibroin microsphere powder is uniformly dispersed in a sodium hyaluronate solution or a modified sodium hyaluronate solution, a cross-linking agent is added to react, and then the mixture is dried and redissolved after swelling and repeated washing, and then crushed, filled and sterilized to achieve injectability, self-supporting properties and a long shaping cycle. The particle size distribution range of the silk fibroin microspheres is 5-200 μm; the surface charge is -50-25 mV; the mass ratio of the silk fibroin and sodium hyaluronate phases in the composite filler is greater than 1; The volume of silk fibroin microspheres in the composite filler accounts for 10-50v / v% of the total volume of the filler; the mass dispersion is 1-50%; the injection force range of the composite filler is 2-50N; the compression modulus of the composite filler is 0.01kPa-500kPa; when the sodium hyaluronate is modified sodium hyaluronate, the silk fibroin microsphere powder is uniformly dispersed in the modified sodium hyaluronate solution, and a chemical initiator or a photocrosslinking agent is added to initiate free radical polymerization, so that covalent crosslinking occurs between the silk fibroin microspheres and the sodium hyaluronate to further obtain a mechanically enhanced composite filler crosslinked by non-covalent bonds and covalent bonds.

[0026] The present invention further protects a method for preparing the above-mentioned injectable composite filler, comprising the following steps:

[0027] (1) dissolving sodium hyaluronate in sodium hydroxide solution and mixing thoroughly until there are no bubbles in the gel, and swelling at room temperature to obtain a sodium hyaluronate solution;

[0028] (2) Add 1,4-butanediol diglycidyl ether to the sodium hyaluronate solution, stir evenly, then add silk fibroin microsphere powder to the blended solution, stir evenly, heat to crosslink, put into water to stir and disperse, filter to separate the gel, crush with a sieve, repeatedly add water to stir, filter, and crush 3-5 times, after washing and swelling are complete, freeze-dry the sample, take the freeze-dried powder and add water to re-dissolve, the re-dissolved sample is crushed with a sieve, filled, defoamed, and sterilized to obtain an injectable composite filler.

[0029] As a further improvement of the present invention, the microspheres are thioketal / calcium-modified silk fibroin microspheres, and the preparation method is as follows:

[0030] U1. Add 100 parts by weight of silk fibroin microspheres to 500 parts by weight of water, add 1-2 parts by weight of calcium chloride, and stir for 10-15 minutes to obtain calcium chelated silk fibroin microspheres;

[0031] U2. Add 10 parts by weight of the calcium chelated silk fibroin microspheres obtained in step U1 to 100 parts by weight of water, add 2-4 parts by weight of citric acid, 10-15 parts by weight of EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide), and 10-15 parts by weight of NHS (N-hydroxysuccinimide), heat to 80-90°C, stir to react for 5-7h, add 3-5 parts by weight of propane-2,2-diylbis(sulfonamide)diethylamine, stir to react for 1-2h, dialyze, and freeze-dry to obtain thioketal / calcium modified silk fibroin microspheres.

[0032] As a further improvement of the present invention, the hydrogel is an induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, and the preparation method is as follows:

[0033] V1. The chitosan was dissolved in 1-2wt% acetic acid solution to obtain a chitosan solution having a concentration of 10-15wt%;

[0034] V2. Dissolve sodium alginate in water to obtain a sodium alginate solution having a concentration of 7-12wt%;

[0035] V3. Sodium hyaluronate was dissolved in 3-5wt% sodium hydroxide solution and mixed thoroughly until there were no aggregated bubbles in the gel, and swelled at room temperature to obtain a 15-20wt% sodium hyaluronate solution;

[0036] V4. Add 1-2 parts by weight of 1,4-butanediol diglycidyl ether to 100 parts by weight of sodium hyaluronate solution, stir evenly, then add 25-30 parts by weight of chitosan solution prepared in step V1, 12-15 parts by weight of sodium alginate solution prepared in step V2, add 2-4 parts by weight of Arg-Gly-Asp gelling agent, stir and mix for 15-20 minutes to obtain induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0037] The present invention further protects a method for preparing the above-mentioned injectable composite filler, comprising the following steps: mixing thioketal / calcium-modified silk fibroin microspheres and induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, uniformly dispersing by ultrasonication, and storing at 4°C to obtain an injectable composite filler.

[0038] The present invention further protects the use of the above-mentioned injectable composite filler in preparing superficial skin and subcutaneous fillers, bone / cartilage repair filling materials or drugs, carriers or scaffolds containing drug components, or biological printing inks for cell-carrying printing.

[0039] In the preparation of superficial skin and subcutaneous fillers, preferably in plastic surgery; stays stably at the injection site as a filler material to reduce skin wrinkles or reshape the skin;

[0040] Application in the preparation of bone / cartilage repair filling materials or drugs; Stable stay at the bone defect site as a scaffold material for bone repair and regeneration;

[0041] Application in the preparation of carriers or stents containing drug ingredients, which are applied to soft tissue trauma or repair filling; the drug ingredients are vitamins, amino acids, mineral elements, microecological regulators, growth factors, small molecule drugs, protein macromolecule drugs, nucleic acid drugs (such as mRNA), antibiotic drugs, hormone drugs, anesthetic drugs, antiviral drugs, antibacterial drugs, anticancer drugs, immunomodulatory drugs or one or more combinations of living cells;

[0042] Or in the application of preparing bioprinting ink for cell-loaded printing, when used, it is mixed with a cell suspension to obtain a cell-loaded colloidal gel, and the above ink is extruded or 3D-printed to obtain a scaffold with a 3D structure, thereby obtaining a cell-loaded printed scaffold.

[0043] The present invention has the following beneficial effects:

[0044] The injectable composite filler prepared by the invention has self-supporting properties, tissue fusion properties, degradability and biosafety, and has broad application prospects.

[0045] 1) High injectability: The gelation critical point of microspheres is high. When the physically cross-linked silk fibroin gel locks the microspheres, the silk fibroin concentration is high (>3%), which will cause the injection force to increase sharply and make injection very difficult. The viscoelasticity advantage of sodium hyaluronate reported in the present invention enables the microsphere system to be stably locked in the cross-linked sodium hyaluronate gel, and under the action of shear injection force, the aggregation between microspheres is avoided, thereby affecting the injectability.

[0046] 2) Controllable mechanical properties: Compared with pure sodium hyaluronate or silk fibroin gel or silk fibroin microspheres, the design of the composite filler system can optimize the ratio between materials or activate the groups between materials to give it a mechanical strength closer to tissue fusion, strong self-support, and improved comfort and natural feel.

[0047] 3) Long-lasting efficacy: The particle size of microspheres is distributed between 5 and 200 μm. Compared with micro-nano particles below 5 μm, they can effectively resist the phagocytosis of macrophages in the body, reduce inflammatory reactions, and slowly degrade while helping collagen regeneration. The advantages of extending degradation time and shaping durability are more prominent.

[0048] 4) Wide application range: The sodium hyaluronate composite filler of silk fibroin microspheres reported in the present invention has good biocompatibility and cell compatibility due to its protein / polysaccharide composition that mimics the composition of the human body. Sodium hyaluronate and silk fibroin can work together: Sodium hyaluronate has the functions of water retention, cartilage repair, and immune regulation, while the introduction of silk fibroin can improve the overall mechanical strength of the material, and has a positive effect on cell adhesion and cell growth, and has more advantages in tissue repair and filling. At the same time, the composite filler can be used as a controlled release carrier for bioactive protein drugs (such as growth factors that induce tissue regeneration), nucleic acid drugs, and mRNA drugs for drug sustained release applications.

[0049] 5) High safety, simple and efficient method: This preparation method is simple and convenient, does not involve the use of toxic organic solvents and surfactants during preparation, avoids the problem of toxic organic solvent and surfactant residues, has low cost, and has high application value for industrial mass production.

[0050] The invention prepares an induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel. In the presence of multiple polysaccharides of chitosan / sodium alginate / sodium hyaluronate, the hydrogel forms a thermosensitive hydrogel. The gelling temperature of the hydrogel is close to body temperature. Therefore, after being injected into the human body, the hydrogel can gel and maintain the elasticity of the face. Before the injection, the hydrogel is in a solution state with high uniformity, and it does not need to be prepared immediately for use, so it is more convenient to use. In addition, by adding an Arg-Gly-Asp gelling agent, the macromolecular chain of the polysaccharide can undergo a conformational change, which can improve the mechanical properties while meeting the needs of cell growth and adhesion, and showing a good promoting effect on the regeneration of capillaries.

[0051] The present invention also prepares thioketal / calcium modified silk fibroin microspheres, which are fixed on the microspheres by chelating calcium ions with carboxyl, amino and hydroxyl groups on amino acids of silk fibroin, and then react with thioketal after activating the carboxyl groups by EDS and NHS, thereby forming stable cross-linked microspheres. In the presence of a large amount of reactive oxygen species (ROS) generated by thioketal in inflammatory cells, the CS bonds of the microspheres are broken, thereby destroying the structure of the microspheres and releasing calcium ions. The released calcium ions can cross-link with the induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel in its matrix, thereby increasing the cross-linking degree of the hydrogel, thereby extending the degradation cycle of the hydrogel, so that the prepared injectable composite filler can maintain its stable state for a long time without being degraded, greatly extending the use time of the injectable composite filler and eliminating the need for frequent injections. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0053] Attached Figure 1 An optical microscope image of the silk fibroin suspension spheres prepared in Example 4 of the present invention;

[0054] Attached Figure 2 is a scanning electron microscope image of freeze-dried silk fibroin microspheres in Example 4 of the present invention;

[0055] Attached Figure 3 is a scanning electron microscope image of the ground and crushed silk fibroin microspheres of Example 9 of the present invention;

[0056] Attached Figure 4 The sodium hyaluronate freeze-dried scaffold containing silk fibroin microspheres according to Example 12 of the present invention;

[0057] Attached Figure 5 is an optical microscope image of the sodium hyaluronate gel filler containing silk fibroin microspheres in Example 12 of the present invention (before sterilization);

[0058] Attached Figure 6 is an optical microscope image of the sodium hyaluronate gel filler containing silk fibroin microspheres in Example 12 of the present invention (after sterilization);

[0059] Attached Figure 7 This is a state diagram of the sodium hyaluronate gel filler containing silk fibroin microspheres after high-temperature sterilization in Example 12 of the present invention being injected through a 26G needle. DETAILED DESCRIPTION

[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1 Preparation of regenerated silk fibroin solution with target molecular weight

[0062] 1. Degumming: Put the mulberry silk into an aqueous solution of sodium carbonate, sodium bicarbonate or a mixed solution of sodium carbonate and sodium bicarbonate, heat and boil, take out and wash with purified water, remove the sericin, and leave the fibroin, dry the degummed fibroin and set aside;

[0063] 2. Dissolving: dissolving the dried silk fibroin in a lithium bromide aqueous solution to obtain a mixed solution containing silk fibroin and a small amount of insoluble particles;

[0064] 3. Purification screening: After the mixed solution is diluted with purified water, it is passed into an ultrafiltration system for desalination, and a system with a retention pore size of the target molecular weight cutoff (50-100kDa, 100-150kDa, 150-200kDa, 200-250kDa) is selected to prepare a regenerated silk fibroin solution with a target molecular weight ((50-100kDa, 100-150kDa, 150-200kDa, 200-250kDa)), and the silk fibroin solubility of the final solution is configured to be 0.1-40w / v%.

[0065] Example 2 Preparation of Silk Fibroin Microsphere Suspension (Blended with Polyethylene Glycol)

[0066] The target molecular weight of the silk fibroin was selected to be 100-150 kDa, the solubility of the solution was 20 w / v%, and it was mixed with polyethylene glycol with a molecular weight of 10 kDa and a concentration of 50 wt% in a volume ratio of 1 / 2, and incubated at room temperature for 2 hours to obtain a stable suspension of silk fibroin microspheres.

[0067] Example 3 Preparation of Silk Fibroin Microsphere Suspension (Blended with Polyvinyl Alcohol)

[0068] The target molecular weight of the silk fibroin was selected to be 200-250 kDa, the solubility of the silk fibroin solution was 20 w / v%, and it was mixed with polyvinyl alcohol with a molecular weight of 10 kDa and a concentration of 5 wt% in a volume ratio of 1 / 4, naturally air-dried at 60°C to form a film, and then dissolved in ultrapure water to obtain a stable suspension containing silk fibroin microspheres.

[0069] Example 4 Preparation of Silk Fibroin Microspheres Aqueous Solution (Dialysis Using Saturated Ammonium Sulfate Solution)

[0070] The target molecular weight of the silk fibroin was selected to be 100-150 kDa, the concentration of the silk fibroin solution was 1 w / v%, and the solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da, and dialyzed in a beaker containing a saturated ammonium sulfate solution (the volume ratio of the silk fibroin solution in the dialysis bag to the saturated ammonium sulfate in the beaker was 1 / 100, and the solution was salted out at room temperature for 2 h to obtain a stable silk fibroin microsphere suspension ( Figure 1 ).

[0071] Example 5 Preparation of Silk Fibroin Microsphere Suspension (Dialysis Using Saturated Ammonium Nitrate Solution)

[0072] The target molecular weight of the silk fibroin was selected to be 100-150 kDa, the concentration of the silk fibroin solution was 1 w / v%, and the solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da, and dialyzed in a beaker containing a saturated ammonium nitrate solution (the volume ratio of the silk fibroin solution in the dialysis bag to the saturated ammonium nitrate in the beaker was 1 / 100, and the solution was salted out at room temperature for 2 h to obtain a stable silk fibroin microsphere suspension.

[0073] Example 6 Preparation of Silk Fibroin Microsphere Suspension (with High Concentration Phosphate)

[0074] The target molecular weight of the silk fibroin was selected to be 100-150 kDa, the concentration of the silk fibroin solution was 0.5 w / v%, and it was mixed with 2 mol / L potassium phosphate solution at a volume ratio of 1 / 1, and incubated at room temperature for 2 h to obtain a stable silk fibroin microsphere suspension.

[0075] Example 7 Preparation of Silk Fibroin Microsphere Suspension (Spray Drying)

[0076] The target molecular weight of the silk fibroin is selected to be 200-250 kDa, the concentration of the silk fibroin solution is 3 w / v%, and the solution is dried by a spray dryer (the aperture of the nozzle is about 40 μm). The dried particles are collected and immersed in a 90% methanol aqueous solution for 10 minutes to form a water-insoluble silk fibroin microsphere suspension.

[0077] Example 8 Washing and Drying of Silk Fibroin Microspheres

[0078] The silk fibroin microsphere aqueous solution in the above-mentioned Examples 2-7 was centrifuged, washed repeatedly for 3 times to remove the denaturation inducer, and then pre-frozen in liquid nitrogen and dried in a freeze dryer to obtain uniformly dispersed silk fibroin microspheres. The particle size of the silk fibroin microspheres was distributed in the range of 5 μm-100 μm. Figure 2 This is a scanning electron microscope image of Example 4 after washing and drying. The particle size distribution range is 5μm-20μm, the microspheres are round and the surface is smooth.

[0079] Example 9 Preparation of Silk Fibroin Microspheres

[0080] The target molecular weight of the silk fibroin was selected to be 100-150 kDa, and the concentration of the silk fibroin solution was 5 w / v%. The solution was placed in an ultrasonic cell crusher for ultrasonication, wherein the ultrasonic amplitude was 75% and the ultrasonic time was 10 minutes. After the ultrasonication, the solution was placed in a 60°C oven for incubation to form a gel. After the gel was formed, the solution was crushed, spread flat on an open plate, and slowly air-dried to form particles. The particles were mechanically ground through a 120-mesh sieve to obtain a silk fibroin microsphere powder ( Figure 3 ).

[0081] Example 10 Preparation of Sodium Hyaluronate Solution

[0082] Weigh 0.3 g of sodium hydroxide particles, add 30 mL of water to prepare a 1% sodium hydroxide solution for later use; weigh 1 g of sodium hyaluronate with a molecular weight of 2200 kDa, add 9 g of the above sodium hydroxide solution, mix thoroughly until there are no aggregated bubbles in the gel, and swell at room temperature for 1 hour; after swelling is completed, set aside.

[0083] Example 11 Preparation of Sodium Hyaluronate Composite Filler Containing Silk Fibroin Microspheres

[0084] Take 10g of 10 wt% sodium hyaluronate solution, add 150μL of 1,4-butanediol diglycidyl ether under low temperature, stir evenly, add 1.2g of silk protein microsphere powder prepared by the method of Example 4 to the blended solution, stir evenly, transfer it into a centrifuge tube, and crosslink it in a 50°C oven for 5h. After crosslinking, put the sample into 2L ultrapure water and stir and disperse it overnight, then separate the gel by suction filtration, crush it with a 60-mesh screen, repeatedly add water and stir, filter, and crush it 3 to 5 times. After washing and swelling, freeze-dry the sample. After freeze-drying, take 0.4g of freeze-dried powder, add 5ml of deionized water for re-dissolution, and the re-dissolved sample is crushed with a 60-mesh screen, filled, defoamed, and sterilized at high temperature and humidity for use.

[0085] Example 12 Preparation of Sodium Hyaluronate Composite Filler Containing Silk Fibroin Microspheres

[0086] Take 10g of 10 wt% sodium hyaluronate solution, add 200μL of 1,4-butanediol diglycidyl ether under low temperature, stir evenly, then add 1.2g of silk fibroin microsphere powder prepared by the method of Example 4 to the mixed solution, stir evenly, transfer it into a centrifuge tube, and crosslink it in a 50°C oven for 5h. After crosslinking, put the sample into 2L ultrapure water and stir and disperse it overnight, then separate the gel by suction filtration, crush it with a 60-mesh screen, repeatedly add water and stir, suction filter, and crush it 3 to 5 times. After washing and swelling are complete, freeze-dry the sample ( Figure 4 ), the porous scaffold of sodium hyaluronate is embedded with uniformly distributed silk fibroin microspheres. 0.4g of freeze-dried sample is reconstituted with 5ml of deionized water, and the reconstituted sample is crushed with a 60-mesh sieve before filling, defoaming, and high-temperature wet heat sterilization for use. Figure 5 It is a composite filler of sodium hyaluronate containing silk fibroin microspheres before high temperature sterilization. Figure 6 It is a sodium hyaluronate composite filler containing silk fibroin microspheres after high-temperature sterilization reaction. After high-temperature sterilization, the silk fibroin microspheres are more evenly dispersed in the gel matrix.

[0087] Example 13 Preparation of Sodium Hyaluronate Composite Filler Containing Silk Fibroin Microspheres

[0088] Take 10g of 10 wt% sodium hyaluronate solution, add 250μL of 1,4-butanediol diglycidyl ether under low temperature, stir evenly, then add 1.2g of silk fibroin microsphere powder prepared by the method of Example 4 to the blended solution, after stirring evenly, transfer it into a centrifuge tube, and crosslink it in a 50°C oven for 5h. After crosslinking, put the sample into 2L ultrapure water and stir and disperse it overnight, then separate the gel by suction filtration, crush it with a 60-mesh screen, repeatedly add water and stir, filter, and crush it 3 to 5 times, after washing and swelling, freeze-dry the sample, take 0.4g of freeze-dried powder after freeze-drying, add 5ml of deionized water for re-dissolution, and the re-dissolved sample is crushed with a 60-mesh screen, filled, defoamed, and sterilized at high temperature and humidity for use.

[0089] Example 14 Preparation of Sodium Hyaluronate Composite Filler Containing Silk Fibroin Microspheres

[0090] Take 10g of 10 wt% sodium hyaluronate solution, add 300μL of 1,4-butanediol diglycidyl ether under low temperature, stir evenly, then add 1.2g of silk fibroin microsphere powder prepared by the method of Example 9 to the blended solution, stir evenly, transfer it into a centrifuge tube, and crosslink it in a 50°C oven for 5h. After crosslinking, put the sample into 2L ultrapure water and stir and disperse it overnight, then separate the gel by suction filtration, crush it with a 60-mesh screen, repeatedly add water and stir, filter, and crush it 3 to 5 times, and freeze-dry the sample after washing and swelling. After freeze-drying, take 0.4g of freeze-dried powder, add 5ml of deionized water for re-dissolution, and the re-dissolved sample is crushed with a 60-mesh screen, filled, defoamed, and sterilized at high temperature and humidity for use.

[0091] Example 15 Injectability Test

[0092] Using the microsphere gel composite filler obtained in Examples 11-14, a colloidal gel with a mass fraction of 8% was prepared with the sodium hyaluronate composite filler containing silk fibroin microspheres in Example 12, loaded into a 1mL syringe, and installed with a 26G injection needle to simulate actual use. The push rod was pushed at a constant pushing speed of 30mm / min, the pushing displacement was 15mm, and the sample in the syringe was pushed out through the needle. Within a certain compression displacement, the compression load of the structural protein / hyaluronic acid composite particle injectable gel ranged from 17 to 24N, the maximum pushing force was 23.932N, and the minimum pushing force was 17.078N. The variation range of the compression load was small, indicating that the sample was evenly dispersed, the injection was smooth, and there was a wire-drawing feel ( Figure 7 ).

[0093] Example 16 Self-healing performance test

[0094] The colloidal gel obtained in Example 15 was loaded into a 1 mL syringe, installed with a 26G injection needle and injected into a 2 mL centrifuge tube. After a period of time, the colloid automatically healed into a whole, and there was no obvious flow phenomenon after being placed upside down for a period of time, indicating that the gel has the potential to be used for facial filling.

[0095] Embodiment 17

[0096] A method for preparing an injectable composite filler comprises the following steps:

[0097] (1) Preparation of thioketal / calcium-modified silk fibroin microspheres, as follows:

[0098] U1. 100 parts by weight of silk fibroin microspheres were added to 500 parts by weight of water, 1 part by weight of calcium chloride was added, and the mixture was stirred for 10 minutes to obtain calcium chelated silk fibroin microspheres;

[0099] U2. Add 10 parts by weight of the calcium chelated silk fibroin microspheres obtained in step U1 to 100 parts by weight of water, add 2 parts by weight of citric acid, 10 parts by weight of EDC, and 10 parts by weight of NHS, heat to 80°C, stir and react for 5 hours, add 3 parts by weight of propane-2,2-diylbis(sulfonamide)diethylamine, stir and react for 1 hour, dialyze, and freeze-dry to obtain thioacetal / calcium modified silk fibroin microspheres.

[0100] (2) Induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, the preparation method is as follows:

[0101] V1. The chitosan was dissolved in 1wt% acetic acid solution to obtain a chitosan solution having a concentration of 10wt%;

[0102] V2. Dissolving sodium alginate in water to obtain a sodium alginate solution having a concentration of 7wt%;

[0103] V3. Sodium hyaluronate was dissolved in 3wt% sodium hydroxide solution and mixed thoroughly until there were no bubbles in the gel, and swelled at room temperature to obtain a 15wt% sodium hyaluronate solution;

[0104] V4. Add 1 part by weight of 1,4-butanediol diglycidyl ether to 100 parts by weight of sodium hyaluronate solution, stir evenly, then add 25 parts by weight of chitosan solution prepared in step V1 and 12 parts by weight of sodium alginate solution prepared in step V2 to the blended liquid, add 2 parts by weight of Arg-Gly-Asp gelling agent, stir and mix for 15 minutes to obtain induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0105] (3) 5 parts by weight of thioketal / calcium-modified silk fibroin microspheres and 50 parts by weight of induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel were mixed, dispersed evenly by ultrasonication, and stored at 4°C to prepare an injectable composite filler.

[0106] Embodiment 18

[0107] A method for preparing an injectable composite filler comprises the following steps:

[0108] (1) Preparation of thioketal / calcium-modified silk fibroin microspheres, as follows:

[0109] U1. 100 parts by weight of silk fibroin microspheres were added to 500 parts by weight of water, 2 parts by weight of calcium chloride were added, and the mixture was stirred for 15 minutes to obtain calcium chelated silk fibroin microspheres;

[0110] U2. Add 10 parts by weight of the calcium chelated silk fibroin microspheres obtained in step U1 to 100 parts by weight of water, add 4 parts by weight of citric acid, 15 parts by weight of EDC, and 15 parts by weight of NHS, heat to 90°C, stir and react for 7 hours, add 5 parts by weight of propane-2,2-diylbis(sulfonamide)diethylamine, stir and react for 2 hours, dialyze, and freeze-dry to obtain thioketal / calcium modified silk fibroin microspheres.

[0111] (2) Induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, the preparation method is as follows:

[0112] V1. The chitosan was dissolved in 2wt% acetic acid solution to obtain a chitosan solution having a concentration of 15wt%;

[0113] V2. Dissolve sodium alginate in water to obtain a sodium alginate solution having a concentration of 12wt%;

[0114] V3. Sodium hyaluronate was dissolved in 5wt% sodium hydroxide solution and mixed thoroughly until there were no bubbles in the gel, and swelled at room temperature to obtain a 20wt% sodium hyaluronate solution;

[0115] V4. Add 2 parts by weight of 1,4-butanediol diglycidyl ether to 100 parts by weight of sodium hyaluronate solution, stir evenly, then add 30 parts by weight of chitosan solution prepared in step V1 and 15 parts by weight of sodium alginate solution prepared in step V2 to the blended liquid, add 4 parts by weight of Arg-Gly-Asp gelling agent, stir and mix for 20 minutes to obtain induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0116] (3) 7 parts by weight of thioketal / calcium-modified silk fibroin microspheres and 70 parts by weight of induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel were mixed, dispersed evenly by ultrasonication, and stored at 4° C. to prepare an injectable composite filler.

[0117] Embodiment 19

[0118] A method for preparing an injectable composite filler comprises the following steps:

[0119] (1) The method for preparing thioketal / calcium-modified silk fibroin microspheres is as follows:

[0120] U1. 100 parts by weight of silk fibroin microspheres were added to 500 parts by weight of water, 1.5 parts by weight of calcium chloride were added, and the mixture was stirred for 12 minutes to obtain calcium chelated silk fibroin microspheres;

[0121] U2. Add 10 parts by weight of the calcium chelated silk fibroin microspheres obtained in step U1 to 100 parts by weight of water, add 3 parts by weight of citric acid, 12 parts by weight of EDC, and 12 parts by weight of NHS, heat to 85°C, stir and react for 6 hours, add 4 parts by weight of propane-2,2-diylbis(sulfonamide)diethylamine, stir and react for 1.5 hours, dialyze, and freeze-dry to obtain thioketal / calcium modified silk fibroin microspheres.

[0122] (2) The preparation method of induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel is as follows:

[0123] V1. The chitosan was dissolved in 1.5wt% acetic acid solution to obtain a chitosan solution having a concentration of 12wt%;

[0124] V2. Dissolve sodium alginate in water to obtain a sodium alginate solution having a concentration of 10wt%;

[0125] V3. Sodium hyaluronate was dissolved in 4wt% sodium hydroxide solution and mixed thoroughly until there were no aggregated bubbles in the gel, and swelled at room temperature to obtain a 17wt% sodium hyaluronate solution;

[0126] V4. Add 1.5 parts by weight of 1,4-butanediol diglycidyl ether to 100 parts by weight of sodium hyaluronate solution, stir evenly, then add 27 parts by weight of chitosan solution prepared in step V1 and 13.5 parts by weight of sodium alginate solution prepared in step V2 to the blended liquid, add 3 parts by weight of Arg-Gly-Asp gelling agent, stir and mix for 17 minutes to obtain induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0127] 6 parts by weight of thioketal / calcium-modified silk fibroin microspheres and 60 parts by weight of induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel were mixed, uniformly dispersed by ultrasonication, and stored at 4°C to prepare an injectable composite filler.

[0128] Comparative Example 1

[0129] Compared with Example 19, the difference is that calcium chloride is not added during the preparation of the thioketal / calcium-modified silk fibroin microspheres.

[0130] Comparative Example 2

[0131] Compared with Example 19, the difference is that during the preparation of the thioketal / calcium-modified silk fibroin microspheres, propane-2,2-diylbis(sulfonamide)diethylamine was not added.

[0132] Comparative Example 3

[0133] Compared with Example 19, the difference is that chitosan was not added during the preparation of the induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0134] Comparative Example 4

[0135] Compared with Example 19, the difference is that sodium alginate is not added during the preparation of the induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel.

[0136] Comparative Example 5

[0137] Compared with Example 19, the difference is that during the preparation of the induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, no Arg-Gly-Asp gelling agent was added.

[0138] Embodiment 20

[0139] The injectable composite fillers prepared in Examples 17-19 and Comparative Examples 1-5 were subjected to performance tests. The results are shown in Table 1.

[0140] In vitro degradation performance. The injectable composite filler is freeze-dried to obtain a dry gel. The dry gel with a weight of m0 is placed in an aqueous solution, and hydrogen peroxide is added to the water to a concentration of 0.5wt%. The degradation test is carried out in an air bath shaker at a temperature of 37°C and an oscillation speed of 150rpm. Take out the sample at regular intervals, freeze-dry it, and weigh it as m1. Then replace it with a new degradation solution. When (m0-m1 / m0) is greater than 0.99, it is considered to be completely degraded. Record its complete degradation time.

[0141] Tensile strength: The tensile properties of the injectable composite filler were tested at room temperature using a CMT4102 universal testing machine. The specimen used in the tensile test had a diameter of 5 mm, a length of 30 mm, and a tensile rate of 50 mm / min.

[0142] Gel time. The gel time was determined by testing the sol-gel transition of the injectable composite filler at room temperature (25°C) and 37°C using the test tube inversion method.

[0143] Table 1

[0144]

[0145] It can be seen from the above table that the injectable composite fillers prepared in Examples 17-19 of the present invention have long degradation time, good mechanical properties, short gelation time, can form hydrogels at 37°C, and do not gel at 25°C, and have temperature-sensitive properties.

[0146] Embodiment 21

[0147] 1. Cytotoxicity

[0148] The injectable composite fillers prepared in Examples 17-19 and Comparative Examples 1-5 were rated according to the United States Pharmacopoeia. The cytotoxicity of all experimental groups was no greater than Grade I.

[0149] Delayed hypersensitivity reaction

[0150] When the injectable composite fillers prepared in Examples 17-19 and Comparative Examples 1-5 were tested according to the method given in GB / T16886.10, no delayed hypersensitivity reaction occurred in any of the experimental groups.

[0151] 3. Intradermal irritation

[0152] When the injectable composite fillers prepared in Examples 17-19 and Comparative Examples 1-5 were tested according to the method given in GB / T 16886.10, the difference between the average score of the test samples in all experimental groups and the solvent control was no more than 1.0.

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An injectable composite filler, characterized in that: The composite filler is composed of microspheres and hydrogels, the particle size distribution range of the microspheres is 5-200 μm, and the surface charge is -50 to 25 mV; The microspheres are thioketal / calcium-modified silk fibroin microspheres, and the preparation method is as follows: U1. Add 100 parts by weight of silk fibroin microspheres to 500 parts by weight of water, add 1-2 parts by weight of calcium chloride, and stir for 10-15 minutes to obtain calcium chelated silk fibroin microspheres; U2. Add 10 parts by weight of the calcium chelated silk fibroin microspheres obtained in step U1 to 100 parts by weight of water, add 2-4 parts by weight of citric acid, 10-15 parts by weight of EDC, and 10-15 parts by weight of NHS, heat to 80-90°C, stir to react for 5-7h, add 3-5 parts by weight of propane-2,2-diylbis(sulfonamide)diethylamine, stir to react for 1-2h, dialyze, and freeze-dry to obtain thioketal / calcium modified silk fibroin microspheres; The hydrogel is an induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, and the preparation method is as follows: V1. The chitosan was dissolved in 1-2wt% acetic acid solution to obtain a chitosan solution having a concentration of 10-15wt%; V2. Dissolve sodium alginate in water to obtain a sodium alginate solution having a concentration of 7-12wt%; V3. Sodium hyaluronate was dissolved in 3-5wt% sodium hydroxide solution and mixed thoroughly until there were no aggregated bubbles in the gel, and swelled at room temperature to obtain a 15-20wt% sodium hyaluronate solution; V4. Add 1-2 parts by weight of 1,4-butanediol diglycidyl ether to 100 parts by weight of sodium hyaluronate solution, stir evenly, add 25-30 parts by weight of chitosan solution prepared in step V1, 12-15 parts by weight of sodium alginate solution prepared in step V2, add 2-4 parts by weight of Arg-Gly-Asp gelling agent, stir and mix for 15-20 minutes to obtain induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel; The preparation method of the injectable composite filler comprises the following steps: mixing thioketal / calcium-modified silk protein microspheres and induced chitosan / sodium alginate / sodium hyaluronate thermosensitive hydrogel, uniformly dispersing by ultrasonication, and storing at 4°C to obtain the injectable composite filler.

2. The injectable composite filler according to claim 1, characterized in that: The preparation method of the silk fibroin microspheres is as follows: S1: preparing a regenerated silk fibroin solution, including the steps of degumming, dissolving and purifying silk, and screening and selecting a regenerated silk fibroin solution with a specific molecular weight through an ultrafiltration system; S2: directly blending the regenerated silk fibroin solution with a specific molecular weight obtained in step S1 with a denaturation inducer, or soaking the solution in a denaturation inducer after rapid drying to obtain a silk fibroin microsphere aqueous solution; S3: centrifuging and repeatedly washing the silk fibroin microsphere aqueous solution prepared in step S2, and then drying the solution to obtain a redispersible silk fibroin microsphere powder; The specific target molecular weight of silk fibroin ranges from 50 to 250 kDa; the concentration of silk fibroin ranges from 0.1 to 40 w / v%, and the denaturation inducer is one or more of alcohols, salts, acids, ketones, nitriles, and furans; the rapid drying method includes spray drying, freeze drying, and natural drying; the blending volume ratio of silk fibroin and denaturation inducer is 1 / 1 to 1 / 1000.

3. The injectable composite filler according to claim 1, characterized in that: The preparation method of the silk fibroin microspheres is as follows: T1: preparing a regenerated silk fibroin solution, including the steps of degumming, dissolving and purifying silk, and screening and selecting a regenerated silk fibroin solution with a target molecular weight through an ultrafiltration system; T2: directly inducing the formation of gel by ultrasound or incubation based on the regenerated silk fibroin solution with a specific molecular weight obtained in step T1; T3: slowly air-drying the silk fibroin gel prepared in step T2 to remove moisture, and then mechanically grinding and pulverizing to obtain redispersible silk fibroin microsphere powder; The specific target molecular weight of silk fibroin ranges from 50 to 250 kDa; the concentration of silk fibroin ranges from 0.1 to 40 wt %; the ultrasonic amplitude ranges from 10 to 100%; and the incubation temperature ranges from 20 to 80° C.

4. Use of the injectable composite filler according to any one of claims 1 to 3 in the preparation of superficial skin and subcutaneous fillers, bone / cartilage repair filling materials or drugs, carriers or scaffolds containing drug ingredients, or bioprinting inks for cell-carrying printing.

Citation Information

Patent Citations

  • Structural protein / hyaluronic acid composite micro-nano particle, particle hydrogel material and application

    CN115521627A

  • Injectable silk protein microsphere gel with adjustable performance and preparation method of injectable silk protein microsphere gel

    CN115671388A

  • Thermosensitive filler composition

    CN113058074A

  • Functional silk fibroin drug carrier and preparation method thereof

    CN113730599A

  • KR20210036130A